Basal insulin requirement in patients with type 1 diabetes depends on the age and body mass index. Issue 2 (3rd May 2021) - Mitsui, Yukari; Kuroda, Akio; Ishizu, Masashi; Mori, Hiroyasu; Kurahashi, Kiyoe; Kondo, Takeshi; Yoshida, Sumiko; Akehi, Yuko; Aihara, Ken‐ichi; Endo, Itsuro; Abe, Masahiro; Matsuhisa, Munehide
Abstract: Aims/Introduction: To investigate the basal insulin requirement in patients with type 1 diabetes who are on multiple daily injections (MDI) and to assess the patient characteristics that affect the percent of total daily basal insulin dose to the total daily insulin dose (%TBD/TDD). Materials and Methods: The subjects of this study were 67 inpatients with type 1 diabetes who were served diabetic meals of 25–30 kcal/kg standard body weight during several weeks of hospitalization. The basal insulin requirement was adjusted to keep the blood glucose level from bedtime to before breakfast within a 30 mg/dL difference. The bolus insulin dose before the meal was adjusted to keep the blood glucose level below 140 and 200 mg/dL before and 2 h after each meal, respectively. The total daily insulin dose (TDD), the percent of total daily basal insulin dose (TBD) to TDD (%TBD/TDD), and clinical characteristics were collected. Results: The median (Q1, Q3) of TDD was 33.0 (26.0, 49.0) units, and the %TBD/TDD was 24.1 ± 9.8%. The %TBD/TDD was positively correlated with the body mass index (BMI) and negatively correlated with the age at the onset and at the examination according to a univariate analysis. However, the %TBD/TDD was dependent on the BMI (β = 0.340, P = 0.004) and the age at examination (β = −0.288, P = 0.012) according to the multiple regression analysis. Conclusions: The average %TBD/TDD in patients with type 1 diabetes on MDI was approximately 24% under inpatient conditions. The basal insulin requirement was dependent on the BMI and the age at examination. Abstract : To investigate basal insulin requirement in patients with type 1 diabetes who are on multiple daily injection therapy (MDI), and to assess the patient characteristics, which affect the percent of total daily basal insulin dose to the total daily insulin dose (%TBD/TDD). The average of %TBD/TDD in patients with type 1 diabetes who are on MDI was approximately 24% under inpatient conditions. The basal insulin requirement was dependent on BMI and age at examination.